Influential factors of spousal relationship quality in couples living with dementia – A narrative synthesis systematic review. (January 2023) - Stedje, Kristi; Kvamme, Tone KS; Johansson, Kjersti; Stensæth, Karette A; Odell-Miller, Helen; Bukowska, Anna; Tamplin, Jeanette; Wosch, Thomas; Baker, Felicity Anne
Aim: The aim of this systematic review is to identify factors that influence relationship quality in couples living with dementia. Previous research has shown how maintaining a positive spousal relationship quality is important for quality of life and coping for both the caregiver and the person with dementia. Knowledge of influential factors could contribute to a deeper understanding of the value of a couple-centred clinical practice and research, within the field of dementia. Research design and methods: Systematic procedures to database search, screening, data extraction and synthesis were followed. Qualitative, quantitative and mixed methods studies were included. A narrative synthesis was conducted through narrative summaries of included studies, thematic analysis and narrative descriptions of factors influencing relationship quality. Results: 39 studies were included in the study: 28 qualitative, 8 quantitative and 3 mixed methods. Through the narrative synthesis, 20 factors were identified. The factors were grouped into two overarching themes: The world of us and The world outside of us, and further to six influencing factor categories: (1) Attitudes and strategies, (2) Behaviour and activities, (3) Emotional connectedness, (4) Activities and experiences outside of the home, (5) Social behaviour and roles, and (6) Belonging and safety. Discussion and conclusion: The identified factors influence relationship quality in couples living with dementia on various levels. The findings of this review study should inform clinical, couple-centred dementia care practise and intervention studies, and further research should seek to gain deeper understandings of the individual factors and broader understandings of the correlations between factors.